2003
DOI: 10.1002/mame.200390009
|View full text |Cite
|
Sign up to set email alerts
|

A Model for the Elastoplastic Behavior of Isotactic Poly(propylene) Below the Yield Point

Abstract: Observations are reported on isotactic poly(propylene) (iPP) in a series of tensile loading‐unloading tests with a constant strain rate at room temperature. A constitutive model is developed for the elastoplastic behavior of a semicrystalline polymer at isothermal uniaxial deformations with small strains. The stress‐strain relations are determined by 5 adjustable parameters which are found by fitting the experimental data. The stress σ (MPa) versus strain ε in a tensile loading‐unloading test with the maximum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2003
2003
2008
2008

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…As the tensile set is accompanied with a temperature rise of the sample a plastic deformation is taking place. The plastic deformation can be due to the deformation of the crystalline domains and/or the amorphous phase [9][10][11][12].…”
Section: Pre-yield Deformationmentioning
confidence: 99%
See 1 more Smart Citation
“…As the tensile set is accompanied with a temperature rise of the sample a plastic deformation is taking place. The plastic deformation can be due to the deformation of the crystalline domains and/or the amorphous phase [9][10][11][12].…”
Section: Pre-yield Deformationmentioning
confidence: 99%
“…The yielding in semi crystalline polymers is very often accompanied by necking with an appreciable temperature rise [4][5][6][7][8]. For PE and PP it has been shown that the assumption that below the yield strain that the deformation in tensile is just nonlinear elastic, it too simple [9][10][11][12]. In cyclic deformation tests at low strains considerable tensile set was observed.…”
Section: Introductionmentioning
confidence: 99%